STATUS KUALITAS AIR SUNGAI SEKITAR KAWASAN PENAMBANGAN PASIR DI SUNGAI BATANG ALAI DESA WAWAI KALIMANTAN SELATAN - Ahmad Rizqan; Idiannor Mahyudin; Mijani Rahman; Jamzuri Hadie (EnviroScienteae, 2016)
This study aimed to analyze the water quality of Sungai Batang Alai. Water quality of physics and chemistry properties were analized in location of sand mining and without sand mining. Research conducted at Sungai Batang Alai Village Wawai District of South Batang Alai Hulu Sungai Tengah. Parameters of physical and chemical of water which analyzed were temperature, TSS, TDS, Debit, BOD, COD, DO, pH, Fe, and Mn. The sample were taken at 4 points with 3x replicatation. Status of water water quality were  determined by using STORET method, then the results were compared with status of river water quality status of Class I based on South Kalimantan Governor Regulation No. 5 of 2007 on the status of river water quality. The results showed that the sand mining activities negatively impact the water quality of the river Batang Alai than the location there are no sand mining. This can be seen by the river water quality status in the area before the sand mining in the category of Class I to Class III down to the location of the existing sand mining.